Saving seeds: The economics of conserving crop genetic resources ex situ in the future harvest centres of the CGIAR - Koo, B.; Pardey, Philip G.; Wright, B.D. (2004)
The conservation of genetic resources is vital to the maintenance of biodiversity and to the world's ability to feed its growing population. There are now more than a thousand genebanks worldwide involved in the ex situ (meaning ”away from the source”) storage of particular classes of crops. Since the 1970s, the eleven genebanks maintained by the centres of the Consultative Group on International Agricultural Research (CGIAR) have become pivotal to the global conservation effort. However, key policy and management issues - usually with economic dimensions - have largely been overlooked. This provided the impetus for a series of detailed economic studies, led by IFPRI, in collaboration with five CGIAR centres: CIAT (based in Colombia), CIMMYT (Mexico), ICARDA (Syria), ICRISAT (India) and IRRI (Philippines). This book reports these studies and discusses their wider implications. (Abstract © CAB ABSTRACTS, CAB International)